2020
DOI: 10.3390/electronics9111808
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Location and Sizing of Distributed Generators in DC Networks Using a Hybrid Method Based on Parallel PBIL and PSO

Abstract: This paper addresses the problem of the locating and sizing of distributed generators (DGs) in direct current (DC) grids and proposes a hybrid methodology based on a parallel version of the Population-Based Incremental Learning (PPBIL) algorithm and the Particle Swarm Optimization (PSO) method. The objective function of the method is based on the reduction of the power loss by using a master-slave structure and the consideration of the set of restrictions associated with DC grids in a distributed generation en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…A 900-kcmil conductor (I max ij = 520 A) was selected for the 21-bus test system based on the operation of the base case (without DGs installed). The voltage bounds of both test systems were set at +/− 10% of the nominal voltage [32]. Because this study addresses the OPF problem, the location of the DGs here is the same as that reported in [17]; therefore, they are located at nodes 9, 12, and 16 in the network.…”
Section: -Node Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A 900-kcmil conductor (I max ij = 520 A) was selected for the 21-bus test system based on the operation of the base case (without DGs installed). The voltage bounds of both test systems were set at +/− 10% of the nominal voltage [32]. Because this study addresses the OPF problem, the location of the DGs here is the same as that reported in [17]; therefore, they are located at nodes 9, 12, and 16 in the network.…”
Section: -Node Systemmentioning
confidence: 99%
“…In this test system, the slack generator produces 4043.1 kW, and the power losses equal 153.85 kW. With respect to the current limits, a 400-kcmil electrical conductor (I max ij = 335 A) was selected for this test system considering a non-telescopic configuration, as well as the same voltage limits used in the 21-bus test system [32]. Finally, the location of the DGs was defined as in [21], i.e., at nodes 26, 61, and 66.…”
Section: The 69-node Systemmentioning
confidence: 99%
“…Nonetheless, due to the presence of binary variables within the location problem, these strategies fail to provide an optimal solution, thus requiring the use of specialized software for their implementation. As a result, the complexity of their solution and its implementation costs increase [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the specialized literature, the analyses of DC networks are made in the context of providing electric distribution applications in urban and rural areas [1,10]. The main approaches correspond to: a) optimal location and sizing of distributed generators in DC grids [11], b) optimal location and operation of battery energy storage systems [12][13][14], c) optimal reconfiguration of DC feeders [15], d) and planning of DC networks [1], among others. Based on the importance of these studies, we focus on the problem of the optimal location and sizing of distributed generators in DC networks considering daily load and PV curves to minimize the number of daily energy losses and the harmful greenhouse gas emissions to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Section 5 describes the main characteristics of the IEEE 33-and IEEE 69-node test feeders as well as the daily load and PV generation curves, respectively. Section 6 presents the numerical results in both test feeders using the CVX tool and the MOSEK solver in the MATLAB programming environment and their comparisons with the GAMS MINLP solvers [11]. Section 7 shows the main conclusions derived from this study and further works.…”
Section: Introductionmentioning
confidence: 99%